2021
DOI: 10.1021/acs.nanolett.0c04550
|View full text |Cite
|
Sign up to set email alerts
|

Remarkably Weak Anisotropy in Thermal Conductivity of Two-Dimensional Hybrid Perovskite Butylammonium Lead Iodide Crystals

Abstract: Two-dimensional (2D) hybrid organic–inorganic perovskites consisting of alternating organic and inorganic layers are a new class of layered structures. They have attracted increasing interest for photovoltaic, optoelectronic, and thermoelectric applications, where knowing their thermal transport properties is critical. We carry out both experimental and computational studies on thermal transport properties of 2D butylammonium lead iodide crystals and find their thermal conductivity is ultralow (below 0.3 W m–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 37 publications
3
39
0
Order By: Relevance
“…As an example, Giri et al reported thermal conductivities of different 2D MHPs through experiments and simulations, where iso-BA 2 PbI 4 exhibited a theoretical thermal conductivity as low as 0.1 W m –1 K –1 . Thermal conductivities which are significantly lower than that of 3D perovskites have been reported to date for several 2D and quasi-2D MHPs, ,,, but it should be noted that there could be significant differences between the samples with same composition but different film preparation methods, and between thin films and single crystals.…”
Section: Thermoelectric Properties Of Metal Halide Perovskitesmentioning
confidence: 80%
See 3 more Smart Citations
“…As an example, Giri et al reported thermal conductivities of different 2D MHPs through experiments and simulations, where iso-BA 2 PbI 4 exhibited a theoretical thermal conductivity as low as 0.1 W m –1 K –1 . Thermal conductivities which are significantly lower than that of 3D perovskites have been reported to date for several 2D and quasi-2D MHPs, ,,, but it should be noted that there could be significant differences between the samples with same composition but different film preparation methods, and between thin films and single crystals.…”
Section: Thermoelectric Properties Of Metal Halide Perovskitesmentioning
confidence: 80%
“…In addition, all-inorganic RP perovskite Cs 2 PbI 2 Cl 2 also exhibited an ultra-low κ value along its c axis of ∼0.37–0.28 W m –1 K –1 in the temperature range 295–523 K, which was attributed to soft layered structure, abundance of low-energy optical phonons, and strong optical–acoustic phonon coupling . At the same time, this material exhibited anisotropic thermal conductivity, which is not unexpected considering the fact that it is all-inorganic, while it has been shown that the orientational effects of bulky organic spacer cations significantly affect out-of-plane thermal conductivity and that complex interactions involving inorganic components and organic spacers can lead to comparable phonon group velocities in both directions for an organic–inorganic 2D MHPs such as BA 2 PbI 4 . In addition, it was shown that for quasi-2D BA 2 MA n ‑1 Pb n I 3 n +1 single crystals, very low κ values (below 0.1 W m –1 K –1 ) could be obtained for RP perovskite single crystals with n = 3–6 .…”
Section: Thermoelectric Properties Of Metal Halide Perovskitesmentioning
confidence: 83%
See 2 more Smart Citations
“…Importantly, the VPVP provides direct information on the local temperature, which opens a possibility of spatiotemporal thermal imaging at both near-equilibrium and far-fromequilibrium conditions, the latter made possible by direct impulsive thermal stimulation of the targeted material with higher-energy MIR pulses than used in this work. We anticipate that the demonstrated VPVP technique can be employed for investigating thermal transport in disordered materials such as organic or polymeric semiconducting films, 49 metal-organic frameworks, 50 covalent organic frameworks, 51 biological materials, 52 and low-dimensional halide perovskites, [53][54][55][56] some of which may not be amenable to high-vacuum deposition of metallic transducers atop.…”
Section: Discussionmentioning
confidence: 99%